Fabrication and investigation of copper rotor bar on 0.5HP induction Motor-A performance and economical study - Ismail, Daut, Prof. Dr.; Gomesh Nair, Shasidharan; Yanawati, Yahya; Nor Shafiqin, Shariffuddin; Muhammad Irwanto, Misrun; Mohd Irwan, Yusoff; Anayet, Karim (Australian Journal of Basic and Applied Sciences, 2012)
Link to publisher's homepage at http://www.insipub.com/